Policing the mobility society: the effects of EU anti-migrant smuggling policies on humanitarianism. (2018) - Carrera, Sergio; Allsopp, Jennifer; Vosyliūtė, Lina
This article examines the ways in which EU's political priority to counter migrant smuggling affect the provision of humanitarian assistance and access to rights to irregular immigrants and asylum seekers. It explores the effects of EU policies, laws and agencies' operations in anti-migrant smuggling actions, and their implementation in two EU member states - Italy and Greece in the context of the 'European refugee humanitarian crisis' during 2015-2017. It shows that the effects of EU and national policies criminalising the facilitation of entry and residence of irregular immigrants extend beyond cases where civil society actors have faced actual prosecutions and criminal convictions when assisting irregular immigrants and asylum seekers. We use the notion 'policing the mobility society' to capture wider punitive dynamics which affect the activities of civil society actors, especially those critically monitoring and politically mobilising for the rights of migrants.